ANALISIS POTENSI PENDAPATAN ASLI DAERAH DAN STRATEGI PENINGKATAN KEMAMPUAN KEUANGAN DAERAH KABUPATEN KEPUALAUAN SELAYAR - Arfah, Aryati; Ramlawati (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
This study aims to (1) evaluate the potential regional income based on Locally Generated Revenue (PAD) in the Selayar Islands Regency, and (2) analyze effective strategies to increase regional financial capacity. The research employs two approaches, qualitative-descriptive and quantitative-descriptive (post-positivistic). The analysis incorporates both primary and secondary data. The research findings show that the potential of Locally Generated Revenue (PAD) of the Selayar Islands Regency is supported by abundant resources. However, the contribution of PAD remains small and is highly dependent on central government transfers. Although there has been some progress in optimizing local taxes, regional levies, and asset management, it has not yet met the expected targets. This study also found the need for more effective strategies to optimize PAD sources, such as utilizing technology for managing local taxes, revitalizing and managing levies in the service sector, and developing the tourism sector to strengthen the region's financial capacity sustainably.